2013
DOI: 10.1152/ajprenal.00590.2012
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences control the susceptibility to ER stress-induced acute kidney injury

Abstract: Endoplasmic reticulum (ER) stress contributes to acute kidney injury induced by several causes. Kidney dysfunction was shown to be influenced by gender differences. In this study we observed differences in the severity of kidney injury between male and female mice in response to tunicamycin, an ER stress agent. Tunicamycin-treated male mice showed a severe decline in kidney function and extensive kidney damage of proximal tubules in the kidney outer cortex (S1 and S2 segments). Interestingly, female tunicamyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 35 publications
6
53
1
Order By: Relevance
“…A mouse model of TM-induced ER stress was induced by a single intraperitoneal injection of TM (2 mg/kg). In this model, it has been reported that male mice show high induction of ER stress markers such as GRP78 and CHOP with proximal tubular damages in outer cortex [27]. Mice were randomly divided into 3 groups: control mice (n = 5), mice with TM injection (n = 5), mice with TM injection plus SRT1720 (n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…A mouse model of TM-induced ER stress was induced by a single intraperitoneal injection of TM (2 mg/kg). In this model, it has been reported that male mice show high induction of ER stress markers such as GRP78 and CHOP with proximal tubular damages in outer cortex [27]. Mice were randomly divided into 3 groups: control mice (n = 5), mice with TM injection (n = 5), mice with TM injection plus SRT1720 (n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, given that the outer medulla expresses ET A receptors, these studies suggest that the ET A receptor is pro-apoptotic in this particular rodent model. Tunicamycin can induce endoplasmic reticulum (ER) stress-and mitochondrial-mediated apoptosis (18), although the direct involvement of ET-1 was not tested in this study. Using the ET B -deficient rat as an experimental model, our group previously reported that pharmacological blockade of the ET A receptor ameliorates tunicamycin-induced renal ER stress and apoptosis in transgenic control rats, while failing to do so in the ET B -deficient rats (8).…”
Section: Working Hypothesis: Endothelium-derived Et-1 Mediates Renal mentioning
confidence: 98%
“…1 This provides short-term protection from acute stress by ( a ) inhibiting global protein translation through phosphorylation of eIF2α, ( b ) increasing ER protein folding capacity through upregulation of ER chaperones, and ( c ) increasing ER-associated degradation. Following acute ischemia and nephrotoxicity (16, 2022), ER stress is induced in kidney epithelial cells both in vivo and in vitro. Overexpression of the ER chaperones BiP/GRP78 (23) and ORP150 (24) or the use of chemical chaperones, such as PBA or TUDCA (25), which enhances the adaptive UPR, dampens the ER stress response by improving protein folding capacity and facilitating the trafficking of unfolded or misfolded proteins, thereby protecting cells and tissues against injury (2325).…”
Section: Pathophysiologymentioning
confidence: 99%